THE USE OF PICTURE SERIES IN TEACHING WRITING RECOUNT TEXT - Yanuarti Apsari (Eltin Journal : Journal of English Language Teaching in Indonesia, 2017)
The objective of the research is to investigate the kind of activities take place during the processof teaching writing recount text through picture series and to identify the benefits that the students obtained from writing recount text through picture series. This research used a qualitative descriptive research method. The respondents of the research are an English teacher and seven grade students of Mts Nurul Hidayah Batujajar. The data were obtained from observation and interview. The results of the study revealed that the teaching writing by using picture series can improve students’ ability in writing recount text. Specifically, they showed some improvement on process of writing and vocabulary. Moreover, the data from observation and interview showed that there are some benefits, which are the development of students’ writing ability, the increasing of students’ participation in the class, fun learning’s atmosphere and the increasing of students’ writing interest.